(3GdeZfis - (3YHO Gddg Hf CMeO Hf eMeO Hf bOGeI GdLeGYjdj GdebOSj Ke GdOeTbj GdMfHdj, ehab GdOjf GHf bOGeI , J (B620 (3gs; (3GdNQbj , YeQ Hf GdMSjf Hf YHO Gddg, CHh GdbGSe,J (B334 (3g` s
(3ChdgG (B:s
(3GdUdM eYGgOI JhUd HfG Edi GdCUdGM Hjf GdeNJdajf UdM Hjf GdeSdejf hCgd GdMQHp s
(3BNQgG (B:s
(3hgh BNQ GdeLdO GdNGeS jJdhg ai GdSGOS cJGH s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B44 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B282s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1626s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs